Integration of Management Information Systems in Marketing Strategies for Enhanced Consumer Engagement - Bahaaudeen, Amirah; Haque, Rasheedul; Jeet, Vikram; Ambreen, Adina (Journal of Posthumanism, 2025)
This study investigates the role of Management Information Systems (MIS) in marketing, specifically in enhancing consumer interactions across diverse organizational contexts. Addressing a notable gap in literature, the research adopts a quantitative methodological approach, utilizing a structured questionnaire administered on 486 marketing professionals operating within technology-intensive, retail, and service-oriented industries and were used as sample of study. To establish the key constructs of MIS utilization in marketing, Exploratory Factor Analysis and Confirmatory Factor Analysis are employed. Furthermore, hypothesis testing is conducted through Pearson correlation analysis, Structural Equation Modeling, Multiple Linear Regression, and One-Way ANOVA, ensuring a robust examination of the relationships between MIS implementation and consumer engagement. The study examines how real-time analytics enables businesses to swiftly adapt to consumer behavior, automated reporting streamlines operational efficiency, data centralization ensures consistency in information accessibility, and DSS enhances strategic decision-making. The moderating effect of industry sector variation is analyzed to determine how different industries experience divergent impacts from these technological implementations. SEM supported all the proposed paths and ANOVA yielded sector variation. It is evident that firms that allocate resources to MIS-oriented initiatives experience heightened consumer engagement. Accordingly, this study examines the latent impact of MIS in shaping marketing strategies to be more dynamic, customized, and data-driven, thereby enhancing the effectiveness of consumer relationship management.